(untitled) (Research, Society and Development, 2021)
The study aimed to describe the aspects of trophic ecology and feeding strategy of the Hassar affinis species in two lakes in the Baixada Maranhense region a wetland of international ecological interest (Site Ramsar). Individuals were collected monthly for one year. 372 stomachs were analyzed, of which 246 were from Lake Cajari and 126 from Lake Viana. The diet composition of the species was analyzed using the Frequency of Occurrence, Volumetric and Food Importance Index method. The result indicated that 49.1% of stomachs had content Lake Cajari. For Lake Viana, the number of stomachs analyzed indicated that 65.8% were full. The most consumed food itens by the species in Cajari were Mollusk of the species Benthonella tenella, Insect larvae of the order Coleoptera, Odonata, Diptera and Ephemeroptera. In Lake Viana, the same items were present. During the dry and rainy season in Lake Cajari there were differences in diet (item/prey) where the species consumed in greater percentage the item Mollusc in the dry period and in the rainy season Insect larvae, however for Viana lake the species did not show significant variation in feeding concerning seasonality. Regarding ontogenetic, H. affinis showed differences in feeding, both in sex and in the maturation stage. Thus, according to the analysis of stomach contents, it was confirmed that the species H. affinis has an omnivorous benthic feeding habit with a generalist strategy, evidencing the importance of the ecosystem for the food chain in both lakes.